2015
DOI: 10.1161/atvbaha.114.304730
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus Impairs Fetal Endothelial Cell Functions Through a Mechanism Involving MicroRNA-101 and Histone Methyltransferase Enhancer of Zester Homolog-2

Abstract: Objective— Gestational diabetes mellitus (GDM) produces fetal hyperglycemia with increased lifelong risks for the exposed offspring of cardiovascular and other diseases. Epigenetic mechanisms induce long-term gene expression changes in response to in utero environmental perturbations. Moreover, microRNAs (miRs) control the function of endothelial cells (ECs) under physiological and pathological conditions and can target the epigenetic machinery. We investigated the functional and expressional effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 42 publications
2
88
2
Order By: Relevance
“…7 In order to investigate how diabetes affects endothelial function and miRs in human endothelial cells, Floris and colleagues took the approach of isolating human umbilical vein endothelial cells (HUVEC) from umbilical cords from pregnancies that were complicated by gestational diabetes (GDM) and from healthy control pregnancies. 8 The use of HUVECs from diabetics and non-diabetics is a clever approach to allow studies of diabetes on freshly isolated human endothelial cells, although it is possible that HUVECs exhibit some differences vis-à-vis endothelial cells involved in vascular complications of diabetes. The authors demonstrated that HUVECs isolated from GDM-complicated pregnancies exhibit increased apoptosis and a reduced ability to form capillary networks, as compared with HUVECs from healthy controls.…”
Section: Novel Pathways For Vascular Cell Perturbations In Diabetesmentioning
confidence: 99%
“…7 In order to investigate how diabetes affects endothelial function and miRs in human endothelial cells, Floris and colleagues took the approach of isolating human umbilical vein endothelial cells (HUVEC) from umbilical cords from pregnancies that were complicated by gestational diabetes (GDM) and from healthy control pregnancies. 8 The use of HUVECs from diabetics and non-diabetics is a clever approach to allow studies of diabetes on freshly isolated human endothelial cells, although it is possible that HUVECs exhibit some differences vis-à-vis endothelial cells involved in vascular complications of diabetes. The authors demonstrated that HUVECs isolated from GDM-complicated pregnancies exhibit increased apoptosis and a reduced ability to form capillary networks, as compared with HUVECs from healthy controls.…”
Section: Novel Pathways For Vascular Cell Perturbations In Diabetesmentioning
confidence: 99%
“…Transcription, translation, and protein degradation are prominent examples of how gene activity is controlled by miRNAs, considered to be “meta-regulators” [22]. Importantly, miRNAs can target epigenetic regulators, which play a role in fetal metabolic programming [23,24], mediating long-term effects on target cells [24,25], and on developing organs and tissues. Epigenetic factors and miRNAs have been shown to be reciprocally regulated [24,25].…”
Section: Micro-intro To the Microrna Worldmentioning
confidence: 99%
“…Importantly, miRNAs can target epigenetic regulators, which play a role in fetal metabolic programming [23,24], mediating long-term effects on target cells [24,25], and on developing organs and tissues. Epigenetic factors and miRNAs have been shown to be reciprocally regulated [24,25]. Thus, miRNAs are recognized as key regulators of diverse biological and developmental processes in eukaryotes (cell proliferation and differentiation, maintenance of tissue identity, apoptosis, immune system development, and responses) and are associated with pathologies, including different types of cancer [26], vascular diseases [27,28], and diabetes [24,29].…”
Section: Micro-intro To the Microrna Worldmentioning
confidence: 99%
“…miR-101 has been implicated in gestational diabetes mellitus. It targets EZH2, a histonelysine N-methyltransferase enzyme at lysine of histone 3 and inactivates the gene [110]. miR-101 has been shown to be upregulated in serum samples collected from Japanese population [84].…”
Section: Mir-101mentioning
confidence: 99%